INDUKSI, PEMBINAAN, DAN PENGEMBANGAN SDM PENDIDIKAN - Sabila Qurrota A'yun; Nadia Putri Kamila; Muhammad Shodiqul Fikri; Junaidah Junaidah; Septuri Septuri (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the development of human resources in Islamic education through induction and coaching programs. This research uses a systematic literature review (SLR) approach with PRISMA method by analyzing articles published between 2020–2025. The results indicate that induction programs play a crucial role in helping new teachers adapt to institutional culture and internalize Islamic values. Meanwhile, coaching programs function as continuous professional development processes that enhance pedagogical, professional, social, and spiritual competencies. The study highlights the importance of integrating induction and coaching within a comprehensive human resource development system. This integration contributes to improving teacher professionalism and strengthening Islamic values in educational institutions. This study proposes an integrative conceptual model that combines induction, continuous coaching, evaluation, and value reinforcement in Islamic education.